2018
DOI: 10.3906/tar-1708-31
|View full text |Cite
|
Sign up to set email alerts
|

Boron and maturity effects on biochemical parameters and antioxidant activity of pepper ( Capsicum annuum L.) cultivars

Abstract: Introduction Boron is an essential element for higher plants. The symptoms of boron deficiency in plants include cessation of root and leaf growth, necrosis of leaf primordia, necrosis of leaf and stem phloem, bark splitting, or reduced pollen germination. There is a narrow range between boron deficiency and toxicity. Typical boron toxicity symptoms occur in the marginal region of mature leaves, whose portions become chlorotic or necrotic (Ozturk et al., 2010). Pepper (Capsicum annuum L.), as a fresh vegetable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 41 publications
1
15
0
1
Order By: Relevance
“…Various health benefits have been found to be related to different Capsicum cultivars. Fresh green peppers and red peppers have ample amounts of vitamin A, C, and antioxidant compounds [ 6 , 11 , 12 , 13 ]. Srinivasan [ 14 ], in his review on the biological activities of capsaicin, documented the various potential anti-carcinogenic, anti-inflammatory, pain relief, weight loss, gastrointestinal, and cardioprotective effects of capsaicin in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Various health benefits have been found to be related to different Capsicum cultivars. Fresh green peppers and red peppers have ample amounts of vitamin A, C, and antioxidant compounds [ 6 , 11 , 12 , 13 ]. Srinivasan [ 14 ], in his review on the biological activities of capsaicin, documented the various potential anti-carcinogenic, anti-inflammatory, pain relief, weight loss, gastrointestinal, and cardioprotective effects of capsaicin in detail.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, both methods base their results on the neutralization of a free radical, which is more representative of the behavior of oxidative stress at biological level. The FRAP test is slightly different from the previous, since it measures antioxidant activity based on the ability that phytochemicals have to act in reducing the Fe 3+ ion to Fe 2+ in acidic conditions (Sarafi et al, 2018). Although, this mechanism does not neutralize an unstable radical, it does provide information about the importance of phytochemicals in the antioxidant activity of biological reactions that generate unstable molecules due to the presence of metals, complexing them and at the same time delaying production of free radicals (Fenton reaction) (Mardani-nejad et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the phytochemical content in edible fruits its related to their health beneficial effects, due to their antioxidant and anti-inflammatory activities, since such compounds may prevent oxidative stress in cells (Rodrigo-García et al, 2011). It has been reported that phenolic compounds present in fruits may affect their color and taste (Sarafi et al, 2018). Carotenoids are responsible for the reddish color at ripening stage.…”
Section: Introductionmentioning
confidence: 99%
“…Studi epidemiologi menunjukkan manfaat dari makanan pedas dalam mengurangi angka kematian dan meningkatkan kualitas kesehatan (Bley et al, 2012;Ly et al, 2015). Ada banyak manfaat nutraceutical yang terkait dengan konsumsi cabai, seperti antiinflamasi (Chen dan Kang, 2013), analgesik (Evangelista, 2015), regulasi glukosa darah (Yang et al, 2014) dan antioksidan (Shahidi dan Ambigaipalan, 2015;Sora et al, 2015;Sarafi et al, 2018). Sifat fungsional sering dikaitkan dengan Capsicum peppers, sebagian besar karena makanan ini menjadi sumber karotenoid (Kim et al, 2016), vitamin C, vitamin E, alkaloid, flavonoid, dan capsaicinoids (Hallmann dan Rembiałkowska, 2012) .…”
Section: Pendahuluanunclassified